The strategy of China in Central Asia - Sharypkazy, N (Journal of Oriental Studies, 2016)
The article considers China’s strategy in the rapidly developing countries of Central Asia. Also, identified China’s interests in this geopolitical region and the main directions of the strategy of China in Central Asia.